Study and assessment of the situations and causes of erosion along the Hau riverbank in An Giang province during the period 2009–2019 - Nguyen, Ngoc Tien; Do, Huy Cuong; Pham, Duc Hung; Pham, Viet Hong; Do, Ngoc Thuc; Nguyen, The Luan; Vu, Duy Vinh (Vietnam Journal of Marine Science and Technology, 2022)
This paper presents the results of applying a statistic, remote sensing (RS) technology, and 3D (three-dimensional) numerical model to study and assess the situations and the causes of riverbank erosion of Hau river in An Giang province during the period 2010–2019, chronologically and spatially. The results show that the erosion of the Hau river in An Giang province during the period 2010–2019 has steadily and widely occurred both in seasons. There is a significant difference in the Hau river’s bank changing compared with the popular one in the past. The riverbank erosion process has occurred increasingly, with solid intensity, in a complex way, and even more in the dry season. It is identified that the causes of the erosion are from hydrological characteristics, river flow dynamics, the geological structure, soil characteristics, and the form of the riverbed and economic - social activities. The finding is a scientific foundation to resolve the riverbank stabilization.